The Effect of Innovation and Technology Towards Economic Growth in Asia - Kusumawardhana, Dhanu (Jurnal Ilmu Ekonomi Terapan, 2020)
This study aims to find out the effects of innovation and technology on economic growth in Asian countries in 2000-2017, and to analyse the different impacts perceived in upper-middle-income countries and lower- middle-income countries in Asia. This study uses data published by the World Bank and WIPO (World Intellectual Property Organization) and uses panel data regression. Patent applications have significant effects on economic growth, both in upper and lower middle-income countries. meanwhile, R&D expenditure has an insignificant effect on economic growth in both clusters. Moreover, estimation results from three other independent variables: FDI, export, and labour show that these three variables have a significant effect on the real GDP of 18 Asian Countries in 2000 - 2017. The results of his study indicate that there is no significant difference of the effects of innovation and technology toward economic growth between upper-middle-income countries and lower-middle-income countries.